Influence of public transport ergonomic features on passenger's functional state - Afonin, Maksym (Видавництво Львівської політехніки, 2020)
The article means an analysis of the passenger transport services quality issue. Researches of public transport routes ergonomic features and their influence on a passenger functional condition are provided. The analysis of such indicators as cabin occupancy rate, noise level, vibration, and acceleration was carried out. Mathematical dependences of the passenger functional condition change considering vehicles ergonomic features were constructed. Threshold values of passenger compartment microclimate, providing the stress index normative values were determined. The most valuable result of the study is a comparative assessment of each type of public transport in terms of comfort and obtaining threshold values of noise, vibration, and acceleration which are acceptable for the normal passenger’s functional condition.
Keywords: ergonomics of rolling stock; noise; vibration; functional state; quality of transport service